Development Strategy for the Astana Gede Edu-Tourism Site in Kawali District, Ciamis Regency, West Java - Efendi, Muhamad Fauzi; Habsah, Ajeng Putu; Yuliana, Aneu Rizky; Putri, Yola Dwi; Fahrudin, Chepy; Astuti, Yani Sri (Jurnal Pendidikan Geografi Unpatti, 2023)
Development is an effort to achieve integration by using and utilizing available resources. One area with good educational potential is the Kawali District, Ciamis Regency. The potential used is in the form of a cultural heritage area based on a historical approach from the saga of the Galuh kingdom at the Pasundan level through the artifacts. Therefore, this research studies the strategy for developing tourism objects at the Astana Gede Site in Kawali District, Ciamis Regency, West Java. The method used in this research is a qualitative approach. Data collection techniques to support research were obtained through field observations, literature reviews, and documentation studies. The analysis uses a SWOT matrix analysis to determine the strengths, weaknesses, threats, and potential of various internal and external influences on the object being studied. This research aims to explain the tourism development strategy at the Astana Gede Site towards optimal development. The study results show that internal and external influences significantly develop these cultural heritage sites. In addition, the urgency of developing these attractions benefits the economy, education, and tourism.